The role and impact of the New Global Protectionism in recent U.S.- China trade relations with illustrations from China’s toy and tire industries - Jie, Zhou (Auckland University of Technology, 2010)
During the recent global recession world trade fell sharply and greater competition has been accompanied by an increase in global protectionism. Global protectionism threatens to restrict the development of trade relations between China and the U.S. The existing literature reveals several sources of trade friction between the two countries. China experienced impacts from the recent global recession as well as from global protectionism. Chinese industries suffered various protectionist measures or safeguard measures imposed by other foreign nations especially the U.S. This research study focuses on an empirical investigation of the impacts of global protectionism on recent trade relations between the two countries with the illustration of impact of these measures on two Chinese industries toys and tires. Based on two hypotheses, the research suggests that U.S. protectionist measures negatively impacted on the toy industry. However, the protectionist impacts on the tire industry appeared to be outweighed by recessionary impacts. Recommendations for strategies that could help avoid or minimize the negative impacts from the global protectionism are made.